Pendidikan Politik Santri Dipondok Pesantren Jabal Rahmah Anau Kadok Talang - Nurul Afizah; dewi dahlan (Politik Islam, 2023)
This research is motivated by the importance of political education among students (santri) of the Jabal Rahmah Anau Kadok Talang Islamic Boarding School. The aim of political education at this boarding school is to shape the character of the students, enabling them to become citizens with ethical and polite political behavior, as well as a deep understanding of political issues. Although there is no specific curriculum for teaching political education, it is integrated through subjects such as Civic Education (PPKN), the activities of the Student Executive Board (BES), discussions, democratic culture practices, and the study of the Prophet's biography (Siroh Nabawiyah). This research employs a qualitative approach, collecting data through in-depth interviews. The objective is to analyze how political education at the Jabal Rahmah Islamic Boarding School shapes the political perspectives and thought patterns of the students, as well as the role of the school leaders in forming the students' political understanding. The research findings indicate that political education at this boarding school focuses on knowledge transfer, consciousness-raising, political identity, and organizational skills development. Through democratic spaces within the Student Council (OSIS) and lectures, the students acquire an understanding of positive political values. The students are also engaged in organizational activities that allow them to develop leadership skills. The political education at this boarding school successfully shapes good behavior, teaches ethical and wise political conduct, and equips the students to respond to political issues. The conclusion drawn from this research is that political education at the Jabal Rahmah Islamic Boarding School effectively molds the character and political understanding of the students. By employing an approach that involves various aspects of knowledge, orientation, behavior, and political action, the political education at this boarding school is capable of producing students who are aware of their rights and responsibilities as citizens, possess political ethics, and can approach political issues wisely. This research provides fresh insights into how political education can shape the character and political perspectives of students, and have an impact on their involvement in political and social life in Indonesia..